Role of semiconductivity and ion transport in the electrical conduction of melanin - Paul Meredith (Proceedings of the National Academy of Sciences, 2012)
Melanins are pigmentary macromolecules found throughout the biosphere that, in the 1970s, were discovered to conduct electricity and display bistable switching. Since then, it has been widely believed that melanins are naturally occurring amorphous organic semiconductors. Here, we report electrical conductivity, muon spin relaxation, and electron paramagnetic resonance measurements of melanin as the environmental humidity is varied. We show that hydration of melanin shifts the comproportionation equilibrium so as to dope electrons and protons into the system. This equilibrium defines the relative proportions of hydroxyquinone, semiquinone, and quinone species in the macromolecule. As such, the mechanism explains why melanin at neutral pH only conducts when “wet” and suggests that both carriers play a role in the conductivity. Understanding that melanin is an electronic-ionic hybrid conductor rather than an amorphous organic semiconductor opens exciting possibilities for bioelectronic applications such as ion-to-electron transduction given its biocompatibility.